Visiting public libraries with young children: an investigation of individual and community factors among caregivers in an area of socio-economic disadvantage. Issue 2 (14th March 2020) - Schmidt, Hanna; Hamilton, Kyra
Abstract: This study examined an extended theory of planned behaviour (TPB), incorporating additional social influences, for predicting parents' and carers' decisions to visit the library with their young children. At Time 1, participants ( N = 212) completed a paper-based questionnaire measuring the TPB constructs as well as group norm, parental role construction, social support (i.e. family and friend support), and psychological sense of community in relation to visiting the library. At Time 2, participants ( N = 171) completed a telephone survey to measure behaviour over the previous six months. Attitude, subjective norm, perceived behavioural control, group norm, and parental role construction predicted intentions. Intentions and perceived behavioural control predicted follow-up behaviour. Results support the TPB and the role of group norm and parental role construction. The findings highlight the importance of social and cognitive factors in predicting parents' and carers' decisions to visit public libraries with their young children.